2004
DOI: 10.1007/s00330-003-1966-9
|View full text |Cite
|
Sign up to set email alerts
|

Detection of colorectal liver metastases: a prospective multicenter trial comparing unenhanced MRI, MnDPDP-enhanced MRI, and spiral CT

Abstract: The aim of this study was to compare unenhanced MRI, MnDPDP-enhanced MRI, and spiral CT in the detection of hepatic colorectal metastases. Forty-four patients with hepatic colorectal metastases were examined with unenhanced and MnDPDP-enhanced MRI and with unenhanced and contrast-enhanced spiral CT. The MR examination protocol included baseline T1-weighted spin-echo (SE), T1-weighted gradient-recalled-echo (GRE), and T2-weighted fast-SE sequences; and T1-weighted SE and T1-weighted GRE sequences obtained 30-60… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
54
0
4

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(61 citation statements)
references
References 33 publications
3
54
0
4
Order By: Relevance
“…with the introduction of second-generation contrast agents and the use of low MI techniques, such as pulse inversion, which allows a continuous sweep with the same bubbles [1][2][3][5][6][7][8][9][10] . The support of gray-scale images is essential to delineate the lesions better and to check the perfect matching of contrast-enhanced and B-mode images.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…with the introduction of second-generation contrast agents and the use of low MI techniques, such as pulse inversion, which allows a continuous sweep with the same bubbles [1][2][3][5][6][7][8][9][10] . The support of gray-scale images is essential to delineate the lesions better and to check the perfect matching of contrast-enhanced and B-mode images.…”
Section: Discussionmentioning
confidence: 99%
“…High-resolution digital contrast-enhanced ultrasound techniques have considerably improved the assessment of malignant and benign tumor lesions in the liver [1][2][3][4][5][6][7][8][9][10][11][12] . Under optimal examination conditions that enable imaging of the entire liver, it is possible to attain a diagnostic reliability comparable to that of contrast-enhanced MRI with a liverspecific contrast agent, and an even higher diagnostic certainty of > 90%, compared with contrast-enhanced multi-detector-spiral CT [1,4,15] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…10, 11). Compared to helical CT multiple studies have shown that MRI with different contrast agents is superior regarding lesion detection and characterization (31,32). MRI is routinely used in patients with unequivocal CT scans or with contraindications to a CT examination.…”
Section: Which Is the Best Modality?mentioning
confidence: 99%
“…In der Darstellung der Gefäßanatomie der Leber, die für eine Operationsplanung essenziell ist, ist die CT anderen Verfahren überlegen, hinsichtlich Detektion und Charakterisierung fokaler Läsionen jedoch die kontrastmittelverstärkte MRT [31][32][33][34][35][36][37].…”
Section: Computertomographieunclassified